The Type and Concentration of Inoculum and Substrate as Well as the Presence of Oxygen Impact the Water Kefir Fermentation Process - Laureys, David; Leroy, Frédéric; Hauffman, Tom; Raes, Marc; Aerts, Maarten; Vandamme, Peter; De Vuyst, Luc (Frontiers in Microbiology, 2021)
Eleven series of water kefir fermentation processes differing in the presence of oxygen and the type and concentration of inoculum and substrate, were followed as a function of time to quantify the impact of these parameters on the kinetics of this process via a modeling approach. Increasing concentrations of the water kefir grain inoculum increased the water kefir fermentation rate, so that the metabolic activity during water kefir fermentation was mainly associated with the grains. Water kefir liquor could also be used as an alternative means of inoculation, but the resulting fermentation process progressed slower than the one inoculated with water kefir grains, and the production of water kefir grain mass was absent. Substitution of sucrose with glucose and/or fructose reduced the water kefir grain growth, whereby glucose was fermented faster than fructose. Lacticaseibacillus paracasei (formerly known as Lactobacillus paracasei), Lentilactobacillus hilgardii (formerly known as Lactobacillus hilgardii), Liquorilactobacillus nagelii (formerly known as Lactobacillus nagelii), Saccharomyces cerevisiae, and Dekkera bruxellensis were the main microorganisms present. Acetic acid bacteria were present in low abundances under anaerobic conditions and only proliferated under aerobic conditions. Visualization of the water kefir grains through scanning electron microscopy revealed that the majority of the microorganisms was attached onto their surface. Lactic acid bacteria and yeasts were predominantly associated with the grains, whereas acetic acid bacteria were predominantly associated with the liquor.